Ontological and scientific-theoretical challenges of contemporary technology. - Kazimierz Rynkiewicz (Studia Teologiczne)
The esay deals with the problem of contemporary technology in retrospect to consciousness and existence. The question of the nature of technology is examined from a semantic and phenomenological perspective. An ontological balance between being and artifical intelligence is relevant. The hermeneutical handling of technology presupposes a theoretical framework with ethical implications. The nature of technology ultimately remains metaphysically closed, like the nature of time.